2023
DOI: 10.3389/fpubh.2023.1229561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and cost of hospitalized patients with asymptomatic COVID-19 in 2020 in Spain

Abstract: IntroductionCOVID-19 transmission has been characterized by the presence of asymptomatic patients. Additionally, most studies evaluating costs focus on symptomatic COVID-19 cases.ObjectiveTo describe the prevalence, characteristics, and costs of asymptomatic COVID-19 cases at admission in Spanish hospitals in 2020.MethodsA nationwide study was performed, and data of hospitalized patients were collected of the Minimum Basic Data Set in Spain during 2020. Patients with COVID-19 codes as a primary and as a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been identified that a large part of the population is asymptomatic of the disease; that is, they do not present any apparent clinical symptoms, which can favor the spread of the infection [ 8 ]. A high prevalence of asymptomatic infections has been documented in various regions worldwide, encompassing countries across Asia, Europe, Africa [ 9 12 ], and the Americas, including Mexico [ 13 ]. These individuals, who are primarily mostly young adults [ 9 , 14 ], workers, health care workers, or household breadwinners may be one of the biggest obstacles in containing the COVID-19 pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified that a large part of the population is asymptomatic of the disease; that is, they do not present any apparent clinical symptoms, which can favor the spread of the infection [ 8 ]. A high prevalence of asymptomatic infections has been documented in various regions worldwide, encompassing countries across Asia, Europe, Africa [ 9 12 ], and the Americas, including Mexico [ 13 ]. These individuals, who are primarily mostly young adults [ 9 , 14 ], workers, health care workers, or household breadwinners may be one of the biggest obstacles in containing the COVID-19 pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%